2019
DOI: 10.3920/qas2018.1451
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic performance, chemical composition and Fusarium verticillioides resistance of Italian white maize varieties

Abstract: White maize varieties were mainly grown in Italy before the advent of hybrids. The characterisation of their nutritional quality and safety will help to enhance the biodiversity of traditional materials, and to exploit it for food production. In fact, in recent years attention has been focused on the use of white maize varieties for the preparation of maizebased gluten-free products for coeliacs. Moreover it is also known that mycotoxin contamination of maize grain is a global threat to the safety of both huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In the context of a climate-changing agricultural scenario, there is an urgent need to discover new sources of adaptation to biotic and environmental stresses that may contribute to crop breeding aimed at maintaining productivity and reducing inputs. To address this objective, landraces can be valuable resources since they are characterized by high genetic variability and they can present favorable alleles for increasing the adaptation to harsh conditions and challenging environments that may have been selected through natural and human pressure [ 15 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of a climate-changing agricultural scenario, there is an urgent need to discover new sources of adaptation to biotic and environmental stresses that may contribute to crop breeding aimed at maintaining productivity and reducing inputs. To address this objective, landraces can be valuable resources since they are characterized by high genetic variability and they can present favorable alleles for increasing the adaptation to harsh conditions and challenging environments that may have been selected through natural and human pressure [ 15 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The two white lines considered in this work (Lo1224w and Lo1446w), although the lack of carotenoid in their kernel, showed an intermediate TAC value (13.27 and 15.30 mmol TE/kg dm, respectively), probably due to the presence of other compounds such as polyphenols. Indeed, recent studies on white Italian landraces [19,20] demonstrated that TAC in white genotypes has comparable values to those found in yellow genotypes, and in the study by Tafuri and co-workers [18] no relation was found between kernel color and SPC. As expected, the TAC value in the black line B73, was one of the highest (20.90 mmol TE/kg dm).…”
Section: Antioxidant Capacity and Soluble Phenolic Contentmentioning
confidence: 95%
“…In the European context, variability in a collection of maize populations from Portugal [15] and Spain [16] have been explored for bread-making purposes. As far as the Italian context, traditional maize germplasm was analyzed with a focus on its richness in biocomponents [17][18] and safety [19][20]. In particular, since the 1970s, the Research Center for Cereal and Industrial Crops in Bergamo has been developing breeding programs with the aim to obtain maize hybrids with a strong adaptation to the Po Valley environment, improving the cold tolerance at the seedling stage and the resistance to Fusarium rot and European corn borer [21].…”
Section: Introductionmentioning
confidence: 99%
“…Maize varieties have been tested in two locations in Italy: Bergamo and Cremona. The FER response after artificial inoculation was rather divergent; however, two varieties (VA117 and VA1213) were identified that had stable resistance in both locations [31]. Another important aspect of relevant research was the identification of genes that play a role in FER resistance, such as the jasmonate-mediated monocot-specific 9-lipoxygenase ZmLOX12 gene, which seems to play a key role in resistance to FER [157].…”
Section: Fusarium Ear Rotmentioning
confidence: 99%